Improving Students’ Reading Comprehension through Peer-Assisted Learning Strategy (PALS) at Grade XI. C of MA Pondok Pesantren Daarun Nahdhah Thawalib Bangkinang (PPDN-TB) - Nurkhairiyah Nurkhairiyah (UIR Press, 2017)
Poor Reading comprehension ability of students at grade XI.C of MA PondokPesantrenDaarunNahdhahThawalibBangkinangwas caused by several factors. One of the main factors was the teaching and learning activities in the class that could not help the students to improve their reading comprehension. In this case, the classroom action research was done to explain to what extent the application of Peer-Assisted Learning Strategy (PALS) to improve the students’ reading comprehension and what factors influence the improvement. The research consisted of two cycles with four meetings for each cycle. All of the students had roles as tutor and tutee. Then, the researcher was helped by a collaborator to observe and give advice about the teaching and learning activities in the class. The research findings showed that the application of PALS improved the students’ reading comprehension. The average score of students before the application of PALS was 59.2 of report text and 57.03 of narrative text. Then, it also improved at the end of cycle 1, 65.38 of report text and 65.45 of narrative text, and the cycle 2, 75.8 of report text and 76.9 of narrative text. The improvement was also influenced by some factors, such as: (1) The students’ willingness to do all of the procedures in PALS. (2) The tutoring activities in the class.(3) The teacher’s roles. In conclusion, the application of PALS better improved the students’ reading comprehension in English at grade XI. C of MA PondokPesantrenDaarunNahdhahThawalibBangkinang.